Connecting Science and Innovation: Insights from EXPOSENA 2023 - Buritica, Alexander; Nasner, Hans (CGIAR, 2023)
On November 28th– 30th in Palmira, Valle del Cauca, EXPOSENA 2023, an esteemed international event, unfolded, drawing collaboration from Cuba, Brazil, Ecuador, and Mexico. This gathering fosters academic, scientific, and cultural exchanges while spotlighting the invaluable role of knowledge acquisition within formative, applied, and technological research projects. These endeavors stand pivotal in realizing the tangible value pledged by the Industrial Biotechnology Center (CBI), addressing the needs of companies and workers in Palmira and its vicinity. They facilitate the integration and advancement of individuals across SENA, productive sectors, and educational realms, all pivotal in bolstering regional, national, and international socio-economic and technological development.